Utilization of chitosan waste in chicken diet - T. Pasaribu; I.P. Kompiang (Jurnal Ilmu Ternak dan Veteriner, 2000)
An experiment has been conducted to determine the possibility of using waste from chitosan processing, which contain shrimp soluble, as poultry feed. The fresh waste was immediately mixed with wheat pollard (1:1, w/w) and sun dried. Another portion of the waste was stored, at low pH (4.5) for 1 month before sun drying. Experimental rations were formulated to be isoprotein (21%) and isoenergy (3000 kcal/kg), with 25% wheat pollard (R1), WPUL 26.3% (R2), wheat polard 12.5% (R3) WPUL 13.2% (R4), WPUB 13.2% (R5). Each ration was fed to 40 doc broiler, divided into 5 cages (4 male and 4 female/cage). Feed and water were given ad lib during the 4 weeks trial period. Body weight gain of treatment R2 (762.8 gram) was significantly (P <0.05) lower than the other treatments, while there was no significant difference between treatment R1 (817.2 gram), R3 (816.0 gram), R4 (839.2 gram) and R5 (830.1 gram). And the FCR values were significantly different (P<0.05) between treatment R2 with R1, R3, R4, and R5, i.e. is 2.43; 2.24; 2.16; 2.16; and 2.06. Respectively it is concluded that chitosan waste, after sun drying and mixed with wheat pollard, could only be included in the formulation up to 13.2%.Key words : Chitosan waste, broiler